Influence of Thermal Properties of Canned Containers and Food Products on the Parameters of the Sterilization Process - Verkhivker, Yakov G; Miroshnichenko, Elena M; Pavlenko, Svetlana I; Altman, Ella I (Edelweiss Applied Science and Technology, 2020)
...